La Importancia de las Herramientas de Colaboración Digitales en la Educación y los Negocios. - Alicia Celina, Leal Cantú; María Elena, Avilez Pineda; Sánchez América, García; Cantú Karina, Martínez (Revista Daena: International Journal of Good Conscience)
In the context of the Fourth Industrial Revolution, digital collaboration tools have become a fundamental resource for educational and business organizations. This study analyzes their impact on communication, project management, and data centralization, highlighting their role in process optimization and decision-making. Digital tools, such as management platforms, shared databases, and analysis systems, not only enhance efficiency and productivity but also foster innovation and competitiveness. In the educational sector, these technologies enable the implementation of active and collaborative methodologies, preparing students for the challenges of an increasingly digitalized environment. In the business sector, they facilitate remote work, improve real-time interaction, and strengthen organizations' responsiveness. This article underscores their relevance as essential pillars in contemporary organizational development.